2019
DOI: 10.1128/jvi.00311-19
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for both Intermittent and Persistent Compartmentalization of HIV-1 in the Female Genital Tract

Abstract: HIV-1 has been shown to evolve independently in different anatomical compartments, but studies in the female genital tract have been inconclusive. Here, we examined evidence of compartmentalization using HIV-1 subtype C envelope (Env) glycoprotein genes (gp160) obtained from matched cervicovaginal lavage (CVL) and plasma samples over 2 to 3 years of infection. HIV-1 gp160 amplification from CVL was achieved for only 4 of 18 acutely infected women, and this was associated with the presence of proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…These types of analyses include virus phylodynamics that provide insights into, for example, intra-host evolution of HIV-1 by estimating the rates of evolution, selection, diversity, divergence, elucidating spatio-temporal distributions of viruses, and identifying number of viral infections. 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of analyses include virus phylodynamics that provide insights into, for example, intra-host evolution of HIV-1 by estimating the rates of evolution, selection, diversity, divergence, elucidating spatio-temporal distributions of viruses, and identifying number of viral infections. 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
“…These types of analyses include virus phylodynamics that provide insights into, for example, intra-host evolution of HIV-1 by estimating the rates of evolution, selection, diversity, divergence, elucidating spatio-temporal distributions of viruses, and identifying number of viral infections. 19,20 To achieve this, we installed a number of phylodynamics programs on the cluster, including Bayesian Evolutionary Analysis by Sampling Trees (BEAST), 21 which uses Bayesian statistical methods that require long computational times and memory requirements. BEAST ran faster on the bioinformatics cluster compared with an ordinary machine (164 and 284 hours, respectively) to complete the same task ( Table 1).…”
Section: Cluster Performance With Computationally Intensive Programsmentioning
confidence: 99%
“…A study on SRLVs compartmentalization performed to date revealed the presence of different viral sequences in the blood, mammary gland, lungs, and central nervous system tissue in clinically affected sheep [6] and in the colostrum and peripheral blood of goats [5,8]. Similarly, compartmentalization has been well documented in the brain, cerebrospinal fluid, and genital tract, as well as in the gut, lung, liver, kidney, and breast milk of patients infected with HIV-1 [34][35][36][37][38]. In the current study, SRLVs sequences from PBLs and milk epithelial cells were genetically similar suggesting an equilibrium of virus between these compartments.…”
Section: Discussionmentioning
confidence: 97%
“…Rare cases have been reported of patients with detectable cervicovaginal lavage (CVL) viral loads despite suppression of blood plasma HIV [66] and partial compartmentalization with partial mixing of infected cells and viruses between the genital tract and the blood [12,[67][68][69]. A few reports found HIV drug resistance profiles in CVL and blood that were discordant [68][69][70].…”
Section: Genital Tract Compartmentalizationmentioning
confidence: 99%